Using information technology to improve surveillance of antimicrobial resistance in South East Asia - Vong, Sirenda; Anciaux, Amaury; Hulth, Anette; Stelling, John; Thamlikitkul, Visanu; Gupta, Sunil; Fuks, Jonas M; Walia, Kāmini; Rattanumpawan, Pinyo; Eremin, Sergey; Tisocki, Klara; Sedai, Tika R; et al. (BMJ (Online), 2017)
Sirenda Vong and colleagues argue that investing in information technology surveillance systems to detect trends is an essential first step in tackling antimicrobial resistance in South East Asian countries